Random walk hypothesis: an application in the emerging stock markets / Nurul Izzati Abdul Hamid - Abdul Hamid, Nurul Izzati (Faculty of Business and Management, 2018)
The emerging stock markets namely Brazil, India, China and Indonesia had become a major players in the economy with large market capitalization of million to trillion per year and rapid growth of GDP, however limited information on how the stock behave whether the future prices can be predicted or not become a major threat to the investors and policy holders. Not only that, the problem with variance ratio test that sometimes are biased due to the severe size distortions and low power and right-skewed infinite samples, resulting in misleading statistical inference. Thus, this lead to the need to investigates the existences of random walk in the emerging stock markets. The objectives of this study are to investigate whether the Brazil, India, China and Indonesia stock market follow the random walk theory or not. This study using the monthly data of stock prices for all four stock market which are Brazilian Stock Exchange (Brazil), Bombay Stock Exchange (India), Shanghai Stock Exchange (China) and Indonesia Stock Exchange (Indonesia) from June 1997 to December 2017. The data was analysed using the Variance Ratio (V R), auto correlation and unit roots test in order to test for the random walk. The study concluded that all the stock markets do follow the random walk theory but at certain lags. This study contributes to the existing literature by providing a study involving part of emerging countries and able to help the investors and policy holders making decisions in their investment in the future.